Maternal profile of mothers giving birth to low birth weight babies: A hospital based cross-sectional study - Abhijit Dutta; Bhaskar Borah Sonowal; Luhit Dhungel (New Indian Journal of OBGYN)
Background: Low birth weight (LBW) is a significant public health problem that affects millions of infants worldwide. The World Health Organisation (WHO) defines LBW as a birth weight of less than 2500 grams. LBW is a global public health problem that affects approximately 15.5% of all births worldwide. LBW is a complex and multifactorial condition that results from a combination of genetic, environmental, and maternal factors. Maternal factors play a critical role in determining the birth weight of infants. Objective: To determine the various maternal factors associated with low birth weight. Materials and methods: This study was a hospital based cross-sectional study conducted among 238 randomly selected term neonates of the postnatal ward of department of Pediatrics, Assam Medical College and Hospital for a period of 2 months. Data were collected with the help of interview technique using predesigned and pretested questionnaires. Data were statistically analysed using chi square test. Results: Among 238 mothers, 46.64% (n=111) had LBW babies. Higher proportions of LBW were found in mothers under 20 years (p=0.049) and weighing less than 45.0 kg (p=0.028). Maternal height (p=0.3009) showed no association. LBW was more prevalent with 1-year birth spacing (p=0.006), BMI ≤ 18 kg/m2 (p=0.049), anemia (p=0.036), and among upper lower class of modified Kuppuswammy scale (p=0.042). Conclusion: Early maternal age, low maternal weight and BMI, maternal anemia, shorter inter-pregnancy intervals and lower socioeconomic status were found to be significant contributors of LBW. These findings highlight the importance of addressing maternal health and socioeconomic factors to reduce the incidence of low birth weight deliveries.